2019
DOI: 10.1167/iovs.19-26585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salidroside on Trabecular Meshwork Cell Extracellular Matrix Expression and Mouse Intraocular Pressure

Abstract: PURPOSE. Excessive accumulation of extracellular matrix (ECM) in the trabecular meshwork (TM) reduces aqueous humor outflow, which likely contributes to elevation of IOP in primary open-angle glaucoma (POAG). Salidroside, a phenolic glycoside isolated from Rhodiola rosea is reported to prevent profibrotic responses by inhibiting Smad signaling pathway activated by TGF-b in liver, lung, and kidney tissues. We tested if salidroside can (1) inhibit TGF-b2induced ECM expression in cultured human TM cells, and (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Similar to our previous findings, 27 the current study demonstrated that TGF-β2 (5 ng/mL) increased both mRNA and protein levels of fibrosis-related ECM molecules, such as FN, COL-IV, and LN, in cultured HTM cells. In this study, we further demonstrated that the TGF-β2–induced expressions of FN, COL-IV, and LN were decreased by osthole in a concentration-dependent manner between 1 and 10 µM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to our previous findings, 27 the current study demonstrated that TGF-β2 (5 ng/mL) increased both mRNA and protein levels of fibrosis-related ECM molecules, such as FN, COL-IV, and LN, in cultured HTM cells. In this study, we further demonstrated that the TGF-β2–induced expressions of FN, COL-IV, and LN were decreased by osthole in a concentration-dependent manner between 1 and 10 µM.…”
Section: Discussionsupporting
confidence: 92%
“…Western blots were performed as previously described. 27 Briefly, 20 µg protein samples were denatured at 100°C for 10 minutes, separated on an 8% or 12% sodium dodecyl sulfate polyacrylamide gel, and transferred to a polyvinylidene difluoride membrane. The polyvinylidene difluoride membrane was washed, blocked with 5% nonfat milk for 1 hour at room temperature, and then incubated overnight at 4°C with primary antibodies, including rabbit polyclonal FN antibody (1:1000; catalog #ab2413; Abcam, Cambridge, MA), rabbit polyclonal COL-IV antibody (1:1000; catalog #ab6586; Abcam), rabbit polyclonal LN antibody (1:1000; catalog #ab11575; Abcam), and rabbit polyclonal GAPDH antibody (1:2000; catalog #ab9485; Abcam).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No fluorescence was detected in the negative control (NC) group (secondary antibodies only) both in MCM and MTM cells ( Figure S1 B). Besides, a number of criteria, including the expression of RSPO4 (spreading throughout the TM but not surrounding tissues ( Patel et al., 2020 )), neuron-specific enolase (NSE), fibronectin (FN), and collagen type IV (Col IV) ( Fan et al., 2019 ; Guo et al., 2012 ; Mao et al., 2013 ; Patel et al., 2020 ), as well as Dex-induced increased expression of myocilin (MYOC) ( Clark et al., 2001 ; Fan et al., 2019 ; Fingert et al., 2001 ), were used to characterize isolated MTM cells. We first studied the expression RSPO4, NSE, FN, and Col IV in MTM cells by immunofluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…A new tip was loaded into the tonometer for every sample group and calibrated prior to measurement. Each measurement was performed in triplicates to account for variability (43).…”
Section: Ocular Toxicity Evaluationmentioning
confidence: 99%